Lack of association between interleukin-18 -607 C/A gene polymorphism and pulmonary tuberculosis in Zahedan, Southeast Iran - Taheri, M; Hashemi-Shahri, S M; Hamzehnejadi, M; Naderi, M; Moazeni-Roodi, A; Bahari, G; Hashemi, M (Prague medical report, 2012)
Interleukin-18 (IL-18) plays a critical role in immune response, contributing to the pathogenesis and pathophysiology of infectious diseases. Polymorphisms in the IL-18 genes are known to influence expression levels and may be associated with outcome of infections. The objective of this study was to determine whether the presence of IL-18 polymorphisms -607 A/C (rs1946518) was associated with tuberculosis disease. We investigated the functional polymorphism of IL-18 (rs1946518) in 174 patients with pulmonary tuberculosis (PTB) and 177 healthy subjects. Genotype analysis was done using tetra amplification refractory mutation system-PCR (T-ARMS-PCR). The allelic and genotypic frequencies of the IL-18 polymorphism did not differ significantly between PTB and the controls. Our finding suggests that IL-18 polymorphism (rs1946518) may not be a risk factor for susceptibility to tuberculosis in a sample of Iranian population. Further studies are required to validate our findings.
Keywords: frekvence genu; plicní tuberkulóza; Interleukin-18; Iran; interleukin-18; Tuberculosis, Pulmonary; genetická predispozice k nemoci; lidé; mužské pohlaví; Female; Genotype; Írán; Male; Genetic Predisposition to Disease; ženské pohlaví; jednonukleotidový polymorfismus; Gene Frequency; Polymorphism, Single Nucleotide; Humans; lidé středního věku; Middle Aged; genotyp